Relations and Links Between Soil Mechanics, Porous Media Physics, Physiochemical Theory, and Effective Medium Theory - Grimstad, Gustav; Ghoreishian Amiri, Seyed Ali; Nordal, Steinar (Frontiers in Physics, 2019)
Modern soil mechanics (geotechnical engineering) was developed as a branch of civil engineering from the 1920’s. While modern porous media physics was developed as a branch of physics and applied mathematics from roughly the same period of time. In soil mechanics the main concern is often on the deformations, resulting from mechanical, hydraulic or thermal actions. In application of porous media physics the main concern is historically on the flow part, putting less emphasis on the mechanical part. However, deformation and flow are highly linked processes, especially in unconsolidated porous media (soil). This paper makes some links between concepts used in porous media physics, like the effective medium theory, and concepts in soil mechanics, like choice of stress measures. As an example, it shows that the use of Terzaghi effective stress is a matter of choice and can be consistently used also for cases where other effective stress measures are used in literature, like Biot effective stress. The requirement, to be consistent, is that the state variables considered, at the constitutive level, includes all relevant variables.